One gene, many proteins: mapping cell-specific alternative splicing in plants - Swarup, Ranjan; Crespi, Martin; Bennett, Malcolm J. (Elsevier, 2016)
Pre-mRNA alternative splicing (AS) generates protein variants from a single gene that can create novel regulatory opportunities. In this issue of Developmental Cell, Li et al. (2016) present a high-resolution expression map of AS events in Arabidopsis root tissues, giving insight into cell-type- and stage-specific AS mechanisms in plants.